Effect of acrylic resins impregnated with uni-directional fiberglass on flexural strength of repaired acrylic resins - Fariba Golbidi; Maryam Amini Pozveh (مجله دانشکده دندانپزشکی اصفهان, 2011)
Introduction: Fractures of acrylic resin dentures are quite common. It is favorable to securely repair the denture to prevent re-fracture. The aim of this study was to evaluate the flexural strength of heat-cured acrylic resin samples repaired with Iranian and foreign self-curing acrylic resins alone and impregnated with uni-directional fiberglass.Materials and Methods: In this experimental study 40 specimens with a dimension of 65×10×2.5 mm were fabricated from Meliodent heat-cured acrylic resin. Eight specimens were left intact as the control group. The other specimens were first fractured and then 8 specimens were repaired with self-curing Acropars acrylic resin; 8 specimens were repaired with self-curing Acropars acrylic resin impregnated with fiberglass; 8 specimens were repaired with self-curing Meliodent acrylic resin and finally, 8 specimens were repaired with self-curing Meliodent acrylic resin impregnated with fiberglass. Then the flexural strengths of repaired and intact specimens were measured by DARTEC machine. The results were analyzed with one-way ANOVA, and Tukey and two-sided Dunett tests (α<0.05).Results: An increase in the flexural strengths was observed only in Meliodent groups repaired with self-curing acrylic resin without fiberglass and with fiberglass (p value < 0.008), with no significant differences between other groups (p value > 0.05). Conclusion: Based on the results of the present study, the use of Acropars and Meliodent self-curing acrylic resin impregnated with fiberglass in repaired site increased the flexural strength only in self-curing Meliodent group. Key words: Acrylic resins, Denture repair, Fiberglass, Polymethyl methacrylate.